2014
DOI: 10.1097/brs.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Neuronal Status in Normal and Cervical Spondylotic Myelopathy Using Diffusion Tensor Imaging

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 22 publications
6
31
0
2
Order By: Relevance
“…Not only a positive correlation between FA at MCL and mJOA score in agreement with previous studies [14,16,18, 26] did we find, but also it is one of the few studies that showed a significant correlation between clinical severity and the mean FA values at total and lesion levels. Indeed, a majority of former studies measured DTI only at MCL and never took other non-compression levels into consideration.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Not only a positive correlation between FA at MCL and mJOA score in agreement with previous studies [14,16,18, 26] did we find, but also it is one of the few studies that showed a significant correlation between clinical severity and the mean FA values at total and lesion levels. Indeed, a majority of former studies measured DTI only at MCL and never took other non-compression levels into consideration.…”
Section: Discussionsupporting
confidence: 93%
“…With the exception of the change at MCL like previous studies [16][17][18] , we found, patients with MCSM had a significant difference in various mean values compared with those in the control group. Probably it will produce increased water mobility and permit water molecules to diffuse toward 73 more directions than in intact axons, where primary diffusion is along a single direction as soon as axons are injured, which must contribute to increased ADC and a loss of anisotropy with decreased FA [16] . So far, no clear conclusion has yet been reached on whether the MCL can be defined as the pathogenic level.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, abnormalities on spinal neuroimaging will continue to provide surrogates of disease activity, with newer modalities potentially gaining higher sensitivity. These include tractography [16][17][18][19] and spectroscopy. 20 The reciprocal relationships of SVA eff ect in patients with kyphosis and those with lordosis may refl ect an optimal spinal alignment to achieve during surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…They found that smoking increased the production and release of inflammatory cytokines, determining decomposition of chondrocyte activity and as a result, disc degeneration. 16 Other factors related to CSM are the presence of Down syndrome, repeated occupational trauma, genetic predisposition and Klippel-Feil syndrome. 17-20 Noteworthy is also the presence of calcification of the posterior longitudinal ligament, complete or incomplete, present in 2% of Japanese and 25% of patients with CSM and due to mutations of inorganic pirofasfatase, which controls calcium metabolism from soft tissues.…”
Section: Pathophysiologymentioning
confidence: 99%